2021
DOI: 10.1186/s13014-021-01899-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pelvic radiotherapy on the gut microbiome and its role in radiation-induced diarrhoea: a systematic review

Abstract: Pelvic radiotherapy is the key treatment for pelvic malignancies, usually including pelvic primary tumour lesions and lymphatic drainage areas in the pelvic region. Therefore, the intestinal tract in the radiation field is inevitably damaged, a phenomenon clinically referred to as radiation enteritis, and diarrhoea is the most common clinical symptom of radiation enteritis. Therefore, it is necessary to study the mechanism of radiation-induced diarrhoea. It has been found that the gut microbiome plays an impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Diarrhea caused by radiotherapy in the pelvic region is mainly caused by intestinal crypt cell apoptosis ( 25 ). In a study of the intestinal crypt in mice, an obvious circadian rhythm was observed in the number of apoptotic cells in the intestinal crypt during the administration of radiotherapy at different times, which indicated that radiotherapy-induced apoptosis occurs in a time-dependent manner ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhea caused by radiotherapy in the pelvic region is mainly caused by intestinal crypt cell apoptosis ( 25 ). In a study of the intestinal crypt in mice, an obvious circadian rhythm was observed in the number of apoptotic cells in the intestinal crypt during the administration of radiotherapy at different times, which indicated that radiotherapy-induced apoptosis occurs in a time-dependent manner ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specific changes in bacterial composition were also reported, although the findings remain inconsistent. Overall, the consensus observation is an increase in phyla Proteobacteria, Fusobacteria and unclassified bacteria and a decrease in phyla Firmicutes and Bacteroidetes and genera Faecalibacterium and Bifidobacterium following pelvic radiotherapy [61,62]. Characteristic pre-radiotherapy microbial compositions were seen in patients who later developed RE during pelvic irradiation [59] or post-radiation diarrhoea [17] and in patients demonstrating improved survival [8].…”
Section: The Gut Microbiota In Radiotherapy and Pelvic Cancersmentioning
confidence: 98%
“…Specific changes in bacterial composition were also reported, although the findings remain inconsistent. Overall, the consensus observation is an increase in phyla Proteobacteria, Fusobacteria and unclassified bacteria and a decrease in phyla Firmicutes and Bacteroidetes and genera Faecalibacterium and Bifidobacterium following pelvic radiotherapy [ 61 , 62 ].…”
Section: The Gut Microbiota In Radiotherapy and Pelvic Cancersmentioning
confidence: 99%
“…In addition to RE, diarrhea is also a common radiation-related intestinal injury. Some studies have observed that pelvic radiotherapy can cause changes in the community composition of the gut microbiota at the level of phyla, order, or genus [ 85 ]. Among them, the potential protective effects of Bifidobacterium , Clostridium cluster XIVa , and Faecalibacterium prausnitzii are reduced, and Enterobacteriaceae and Bacteroidetes are increased, which may especially lead to diarrhea [ 86 ].…”
Section: Interactions Between Gut Microbiota and Radiotherapymentioning
confidence: 99%